Dissociation of ⟨111⟩ dislocations on {11¯0} in pentaerythritol tetranitrate. Issue 9 (3rd May 2019) - Cawkwell, M. J.; Mohan, N.; Luscher, D. J.; Ramos, K. J.
ABSTRACT: Plastic deformation in the tetragonal explosive molecular crystal pentaerythritol tetranitrate (PETN) is mediated in part by dislocations with Burgers vector⟨ 111 ⟩ on{ 1 1 ¯ 0 } . This observation is unexpected since⟨ 111 ⟩ is the longest possible Burgers vector in PETN. Moreover, plastic slip on the{ 1 0 1 ¯ } planes has not been observed. The generalised stacking fault energy surface for PETN( 1 1 ¯ 0 ) has been computed using dispersion-corrected density functional theory that identified a metastable stacking fault for the displacement1 / 2 [ 111 ] . The stacking fault energy computed with full relaxation of the atomic positions is 83.5 mJ/m 2 . This result indicates that dislocations with Burgers vector⟨ 111 ⟩ split into two partial dislocations with Burgers vector1 / 2 ⟨ 111 ⟩ on{ 1 1 ¯ 0 } with an equilibrium separation of about 35 and 53 Å for the screw and edge dislocations, respectively. Steric hindrance between molecules render the1 / 2 ⟨ 111 ⟩ stacking fault unstable on{ 10 1 ¯ }, which prevents the dissociation of⟨ 111 ⟩ dislocations on these planes and accounts for why this slip system is not seen experimentally.